2017
DOI: 10.1080/14767058.2017.1297407
|View full text |Cite
|
Sign up to set email alerts
|

Bakri balloon versus condom-loaded Foley’s catheter for treatment of atonic postpartum hemorrhage secondary to vaginal delivery: a randomized controlled trial

Abstract: Condom-loaded Foley's catheter is as effective as Bakri balloon in the management of primary atonic PPH following vaginal delivery but requires a significant bit longer time to stop the attack.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 20 publications
0
47
0
1
Order By: Relevance
“… 9 One randomised controlled trial showed that the condom-catheter device is as effective as the Bakri balloon but requires a significantly little longer time to stop the bleedings. 18 However, advanced maternal age and caesarean section are associated with lower success rates. 19 The present trial does not exclude the possibility that the condom-catheter device could be effective in settings where access to surgery is more difficult than in capital cities as Cotonou or Bamako.…”
Section: Discussionmentioning
confidence: 99%
“… 9 One randomised controlled trial showed that the condom-catheter device is as effective as the Bakri balloon but requires a significantly little longer time to stop the bleedings. 18 However, advanced maternal age and caesarean section are associated with lower success rates. 19 The present trial does not exclude the possibility that the condom-catheter device could be effective in settings where access to surgery is more difficult than in capital cities as Cotonou or Bamako.…”
Section: Discussionmentioning
confidence: 99%
“…Balloon tamponade has been suggested as an alternative method, which can significantly control PPH [4]. The efficacy of Bakri balloon tamponade has also been reported in various studies as a new tool to control PPH with a high success rate [5].…”
Section: Introductionmentioning
confidence: 98%
“…surgical intervention or uterine artery embolisation) associated with UBT introduction . Most research on UBT in high‐resource settings has evaluated costly devices such as the Bakri balloon, but a similar effect can be achieved using the low‐cost alternative of tying a condom to the end of a urinary catheter . A 2013 review of UBT in LMIC (mostly using condom‐catheter devices) reported that bleeding was controlled after UBT for 234/241 (97.1%) women .…”
Section: Introductionmentioning
confidence: 99%